DETECTION OF SOMATIC MUTATIONS IN THE BRAF GENE BY PYROSEQUENCING - O. P. Dribnokhodova; E. A. Dunaeva; G. V. Leshkina; E. A. Yarygina; A. Yu. Bukharina; Ya. A. Voiciehovskaya; E. V. Borisova; S. K. Bormotova; A. I. Daoud; V. N. Khlavich; K. O. Mironov (Сибирский онкологический журнал, 2021)
Introduction. Detection of somatic mutations in the BRAF gene can be used in clinical oncology to clarify the diagnosis, select therapy and assess the prognosis of the disease. Pyrosequencing technology makes it possible to identify both already known and new mutations, as well as to determine the mutant allele ratio in the sample.The aim of the study was to develop the pyrosequencing-based method for detecting mutations in 592–601 codons of the BRAF gene.Material and Methods. The nucleotide sequences were obtained using «PyroMark Q24» instrument. The sensitivity and specificity of the method were estimated using dilutions of plasmid DNA samples containing the intact BRAF gene fragment mixed with sequence containing one of the mutations V600E, V600R, V600K, V600M, and K601E. The clinical testing was performed on 200 samples from thyroid nodules.Results. The developed method makes it possible to determine samples containing 2 % of the mutant allele for mutations V600K and V600R, 3 % for V600E and V600M, and 10 % for K601E. The pyrogram signal values for samples without mutations ranged from 0 to 19.5 % for different mutations. An analysis algorithm was developed to confirm the presence and differentiation of mutations in the 600 codon at a low proportion of the mutant allele based on the signals ratio on the pyrogram. The 47 clinical samples with mutations were found, 45 with V600E and 1 with V600_K601>E, for one sample, the type of mutation in the 600 codon could not be determined. The proportion of the mutant allele was 3.5–45 %. The concentration of extracted DNA less than 10 copies per mkl was obtained in 47 samples, of which 8 samples were found to have the mutations.Conclusion. The pyrosequencing-based method was developed for the detection of somatic mutations in 592–601 codons of the BRAF gene. The technique provided sufficient sensitivity to detect frequent mutations in the 600 codon and allowed the detection of rare mutations. Extraction of DNA from clinical samples obtained by fine-needle aspiration biopsy in most cases provided a sufficient concentration of DNA, which made it possible to use the technique in combination with cytological analysis without additional sampling. This approach can be applied to determine somatic mutations in DNA fragments of same length for other oncogenes.